2000
DOI: 10.1093/toxsci/57.1.75
|View full text |Cite
|
Sign up to set email alerts
|

Oral Bioavailability and Pharmacokinetics of Elimination of 9-Hydroxybenzo[a]pyrene and Its Glucoside and Sulfate Conjugates after Administration to Male and Female American Lobsters, Homarus americanus

Abstract: The pharmacokinetics of [(3)H]-9-hydroxybenzo[a]pyrene (9-OH-BaP), a highly lipophilic primary metabolite of benzo(a)pyrene, were examined after intrapericardial (iv) or oral doses of 50 or 200 microg/kg to intermolt American lobsters, Homarus americanus. Combining data for all lobsters, the average terminal elimination half-life of parent 9-OH-BaP was 97.3 h after iv and 56.5 h after oral administration, considerably less than found previously for benzo(a)pyrene (720 h). The oral bioavailability of parent 9-O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2003
2003
2008
2008

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 40 publications
0
7
0
Order By: Relevance
“…As there are significant differences in physiological rates associated with the major moulting stages, crustacean physiological studies generally suggest that animals in one or another stage of the moulting cycle (intermoult) be used only when they are in physiological equilibrium (Carvalho & Phan, 1998). For example, Li and James (2000) standardized their samples by using intermoult stage lobsters. However, there have been no known sample standardizations previously in pharmacokinetic studies of culture shrimps (Park et al.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As there are significant differences in physiological rates associated with the major moulting stages, crustacean physiological studies generally suggest that animals in one or another stage of the moulting cycle (intermoult) be used only when they are in physiological equilibrium (Carvalho & Phan, 1998). For example, Li and James (2000) standardized their samples by using intermoult stage lobsters. However, there have been no known sample standardizations previously in pharmacokinetic studies of culture shrimps (Park et al.…”
Section: Resultsmentioning
confidence: 99%
“…when they are in physiological equilibrium (Carvalho & Phan, 1998). For example, Li and James (2000) standardized their samples by using intermoult stage lobsters. However, there have been no known sample standardizations previously in pharmacokinetic studies of culture shrimps (Park et al, 1995;Reed et al, 2004;Sangrungruang et al, 2004;Uno, 2004), and these studies all show considerable variability in hemolymph drug concentrations.…”
Section: Otc Pharmacokinetics In the Digestive Glandmentioning
confidence: 99%
“…Though based on a triplicate measure of the pooled gut fluid sample, the mass balance for gut fluid presented here seems only to suggest that the relative distribution of pyrene-derived compounds in gut fluid resembles that of tissue. In a study of 9-OH-BaP, a highly lipophilic primary metabolite of BaP, in American lobster (Homarus americanus), Li and James [35] found that 9-OH-BaP was readily conjugated to sulfate and glucose and that, despite its high lipophilicity, 9-OH-BaP was excreted from the lobster hemolymph and tissue much more rapidly than BaP. More studies concerning the pharmacokinetics of hydroxylated PAH and their metabolic conjugates in individual animals are needed to identify if this holds true in tissue and gut fluid of deposit-feeding marine invertebrates.…”
Section: Discussionmentioning
confidence: 99%
“…Identification of these compounds was based on their susceptibility to hydrolysis by sulfatases. Few studies have measured in vitro sulfation in crustaceans (Li and James 2000;de Knecht et al 2001). In vitro sulfation of steroid hormones occurs at rather highmetabolic rates in echinoderms, but not in molluscs or crustaceans (Janer et al 2005c).…”
Section: Sulfotransferasesmentioning
confidence: 99%